Moderating effect of knowledge entrepreneurship in the relationship between knowledge management process and entrepreneurial success - Ruixue Zhang (Journal of Innovation & Knowledge (JIK), 2025)
This study explores the moderating effect of knowledge entrepreneurship (KNE) on the relationship between knowledge management process subsystems (KMPS) and entrepreneurial success (ENS) within China's information technology (IT) industry, thus elucidating the intricate dynamics of knowledge management in this rapidly evolving IT sector and offering a novel perspective on KNE's role. Employing a convenient sampling technique and cross-sectional design, data are collected through a self-administered questionnaire from professionals in the field and analyzed using structural equation modeling. The findings reveal that knowledge acquisition exerts a positive and significant impact on ENS, paralleled by the similarly positive and substantial influence of knowledge conversion. In addition, both knowledge preservation and utilization have beneficial and considerable impacts on ENS, highlighting the multifaceted nature of knowledge management processes (KMP). Notably, KNE significantly enhances the effect of the four KMPS dimensions on ENS. Overall, this research not only substantially contributes to the literature, particularly by examining KNE's moderating role in the interaction between KMPS and ENS, but also provides a comprehensive analysis of the symbiotic relationship between these factors. It expands the research landscape by providing insights into the complex mechanisms through which knowledge management and entrepreneurship interact within the IT sector. Furthermore, the findings offer practical relevance to managers and policymakers, underscoring the critical importance of effective knowledge management practices in fostering ENS. Finally, this study serves as a valuable resource for future researchers, extending research horizons and understanding how knowledge-driven strategies can be effectively leveraged for business success in the dynamic and rapidly evolving IT industry.
Keywords: O32; O33; O34; O38; M13; 650; Entrepreneurial success; IT Industry; Knowledge entrepreneurship; Knowledge management process; Structural Equation Modeling